Implementing standing orders on disaster (SOD) at Union level: the case of Kakua Union, Tangail district and Kazipur Union of sirajganj district, Bangladesh - Rashid, Mohammad Harunor (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2008.